Is there any Relationship between Sleeping Position and Varicocele? - Mehrabi, Sadrollah; Bazarganipour, Fatemeh; Heidari, Zahra; Taghavi, Seyed Abdolvahab (Urology Journal, 2026)
Purpose: Varicocele is the abnormal dilatation of the veins of the pampiniform plexus, which is considered one of the most common factors related to infertility in men. The aim of the present study was to investigate whether a relationship exists between sleeping position and the presence of varicocele. Materials and Methods: In this case-control study, 231 adult infertile men who were referred to the Kowsar Infertility Center, Yasuj, Iran, were divided into two groups: a control group including 113 infertile patients without varicocele, and a case group of 118 infertile patients with varicocele. After the first visit by the urologist and determining the presence or absence of varicocele, as well as the clinical grading of the varicocele, the patients completed demographic, clinical, and sleep position questionnaires. Results: The findings of the current study indicated a significant relationship between the presence of varicocele and the faller-down (lying on the abdomen) sleeping position. There was also a significant positive correlation between this position and the degree of varicocele (p =0.003). Conclusion: The faller-down or prone position during sleep has a meaningful relationship with varicocele, which may be due to increased intra-abdominal pressure. More studies are needed to confirm this hypothesis.